2020
DOI: 10.3390/polym12061340
|View full text |Cite
|
Sign up to set email alerts
|

New Carbon Nanofiber Composite Materials Containing Lanthanides and Transition Metals Based on Electrospun Polyacrylonitrile for High Temperature Polymer Electrolyte Membrane Fuel Cell Cathodes

Abstract: Electrospinning of polyacrylonitrile/DMF dopes containing salts of nickel, cobalt, zirconium, cerium, gadolinium, and samarium, makes it possible to obtain precursor nanofiber mats which can be subsequently converted into carbon nanofiber (CNF) composites by pyrolysis at 1000–1200 °C. Inorganic additives were found to be uniformly distributed in CNFs. Metal states were investigated by transmission electron microscopy and X-ray photoelectron spectroscopy (XPS). According to XPS in CNF/Zr/Ni/Gd composites pyroly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 67 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…It may happen because ascorbic acid is quite acidic due to the ascorbate ion resonance stabilization, therefore, ascorbic acid can coordinate platinum ions and the surface of the composite CNF, leading finally to the better attachment of the Pt nanoparticles to the CNF surface. In our previous studies [26,28], it was shown that Zr and Ni are mostly in forms of ZrO x and Ni 0 in pyrolyzed polyacrylonitrilebased composite CNF. The coincidence of Zr and Pt in addition to Ni on elemental maps may suggest the mentioned mechanism of Pt attachment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It may happen because ascorbic acid is quite acidic due to the ascorbate ion resonance stabilization, therefore, ascorbic acid can coordinate platinum ions and the surface of the composite CNF, leading finally to the better attachment of the Pt nanoparticles to the CNF surface. In our previous studies [26,28], it was shown that Zr and Ni are mostly in forms of ZrO x and Ni 0 in pyrolyzed polyacrylonitrilebased composite CNF. The coincidence of Zr and Pt in addition to Ni on elemental maps may suggest the mentioned mechanism of Pt attachment.…”
Section: Discussionmentioning
confidence: 97%
“…Earlier [26][27][28][29][30][31][32][33][34][35][36][37][38] we have shown that more durable, compared with carbon black, CNF-based materials, including Pt-Ni-ZrO x /CNF, can be used as cathodes in membraneelectrode assembly (MEA) for HT-PEMFC.…”
Section: Introductionmentioning
confidence: 99%
“…ZrO x and Ni(0) introduced into the PGM electrode interact with PA to create more active sites [305]. Carbon nanofiber (CNF) composites doped with Zr/Ni/Gd have been proposed to create phosphate metal species on which the electrode material (Pt) is then deposited [306]. These proton-conducting fillers improve the catalyst layer proton conductivity and hinder acid (PA) leaching.…”
Section: Pa Diffusion In the Electrodementioning
confidence: 99%
“…In another work, Pt-metal/carbon nanofibers and Pt-metal oxide/carbon nanofiber catalytic systems were proposed by Ponomare’s group as gas diffusion electrodes [ 76 ]. Platinated carbon nanofiber (CNF) composites were successfully used as cathodes in the membrane-electrode assembly under high-temperature polymer electrolyte membrane fuel cell experiment.…”
Section: Energy Conversionmentioning
confidence: 99%